3D Ag(I) coordination polymer constructed from a flexible pyridyloxycyclotetraphoshazene linker: Synthesis, crystal structure and dye adsorption properties. (1st February 2023) - Davarcı, Derya; Duyar, Ceyda; Zorlu, Yunus
Graphical abstract: The reaction of the flexible polydentate ligand octakis(3-pyridyloxy)cyclotetraphosphazene (O3 PyCP) with AgNO3 afforded a new coordination polymer, [Ag2 (O3 PyCP)](NO3 )2 ]n (1 ). The resultant 3D coordination polymer was characterized by single-crystal X-ray crystallography. The study of dye adsorption for tetramer-based 3D coordination polymers was carried out for the first time in this study. Dye adsorption investigations indicated that compound 1 adsorbs anionic methyl orange (MO) from water, whilst it did not show any adsorption behaviour against cationic methylene blue (MB). Abstract: The reaction of the flexible polydentate ligand octakis(3-pyridyloxy)cyclotetraphosphazene (O3 PyCP) with AgNO3 afforded a new coordination polymer, [Ag2 (O3 PyCP)](NO3 )2 ]n (1 ). The resultant coordination polymer was characterized by single-crystal X-ray crystallography and infrared spectroscopy. The ligand O3 PyCP acts in the κ 6 N coordination mode by connecting six Ag(I) ions to form a 3D coordination framework. Topological analysis confirms that compound 1 shows a 3D structure with a fsc topology with the vertex symbol of {4 4 .6 10 .8}{4 4 .6 2 }. The thermal stability of O3 PyCP and compound 1 were investigated by thermogravimetric analysis. The study of dye adsorption by tetracyclophosphazene-based coordination polymers was carried out for the first time in this study. According to dye adsorption studies, compound 1 adsorbs anionic methyl orange (MO) from water, but does not exhibit any adsorption behaviour toward cationic methylene blue (MB). A pseudo-second-order kinetic model is suitable to explain the adsorption kinetics.